Avaliação de frações antigênicas de Strongyloides venezuelensis obtidas por hidrofobicidade, no imunodiagnóstico da estrongiloidíase humana - Feliciano, Nágilla Daliane (2010)
Human strongyloidiasis is an intestinal parasitosis of worldwide importance, is asymptomatic in 50% of infected individuals, however, can cause hyperinfection and dissemination in immunosuppressed patients. The use of accurate diagnosis is very important for identification and control of this disease. The use of fractionated antigens has enabled the development of diagnostic tests more reliable, the sensitivity and specificity greater than total extracts. The aim of this study was to characterize and compare the total saline extract (ES) and alkaline (EA) of Strongyloides venezuelensis and their fractions detergent (ESD and EAD) and aqueous (ESA and EAA) in the immunodiagnosis of human strongyloidiasis. The antigenic fractions were obtained from the ES and EA extracts by fractionation with Triton X-114 and tested in serum samples to detect IgG by ELISA and by immunoblotting (IB). We analyzed 120 serum samples: 40 patients with strongyloidiasis (Group 1), 40 patients with other parasitic infections (Group 2) and 40 apparently healthy individuals (Group 3). Parasitological tests Baermann-Moraes and Lutz were performed with three samples of faeces per individual for identification or not of intestinal parasites. We calculated the sensitivity, specificity and diagnostic efficiency of each test employed for each antigenic preparation. Sensitivities and specificities of ELISA were 90% and 90% (ES), 95% and 95% (ESD), 90% and 90% (ESA), 92.5% and 93.8% (EA), 87.5% and 88.8% (EAD) and 77.5% and 78.8% (AAS) respectively and the IB were 95% and 92.5% (ES), 95 and 97.5% (ESD), 82 , 5% and 97.5% (ESA), 90% and 95% (EA), 92.5% and 95% (EAD) and 45% and 100% (AAS). In IB each extract showed a different profile of immunodominant antigenic components with variations between bands of apparent molecular weight of 126, 126-90, 90, 55, 45-41, 45-33, 33 and 28 kDa. The efficiency of diagnosis for the ELISA and IB for each extract were 90% and 93.3% (ES), 95% and 96.7% (ESD), 90% and 92.5% (ESA), 93.3% and 93.3% (EA), 88.3% and 94.2% (EAD) and 78.3% and 81.7% (AAS). The detergent fraction obtained of total salt extract of S. venezuelensis showed better diagnostic efficiency in both tests and is recommended as an alternative antigen in the immunodiagnosis of human strongyloidiasis.